Терракотовые статуэтки крылатого юноши в Северном Причерноморье (иконография и вопросы интерпретации) - Савельева, Е.С. (Материалы по археологии Северного Причерноморья, 2011)
Target of research is a group of terracotta statuettes representing a winged young man which have got different explanations in scientific literature. The statuettes of that type were found in ancient centers of the North-Western and Northern Black Sea. The matters of the statuettes' interpretation, dating and origin are considered. Terracottas conveying the same motif in the similar monographic scheme are used as analogies.